Answer:
![\displaystyle x= -\frac{10}{\sqrt{269}}\\\\\displaystyle y= \frac{13}{\sqrt{269}}\\\\\displaystyle z = \frac{23\sqrt{269}+269}{269}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20x%3D%20-%5Cfrac%7B10%7D%7B%5Csqrt%7B269%7D%7D%5C%5C%5C%5C%5Cdisplaystyle%20y%3D%20%5Cfrac%7B13%7D%7B%5Csqrt%7B269%7D%7D%5C%5C%5C%5C%5Cdisplaystyle%20z%20%3D%20%5Cfrac%7B23%5Csqrt%7B269%7D%2B269%7D%7B269%7D)
<em>Maximum value of f=2.41</em>
Step-by-step explanation:
<u>Lagrange Multipliers</u>
It's a method to optimize (maximize or minimize) functions of more than one variable subject to equality restrictions.
Given a function of three variables f(x,y,z) and a restriction in the form of an equality g(x,y,z)=0, then we are interested in finding the values of x,y,z where both gradients are parallel, i.e.
![\bigtriangledown f=\lambda \bigtriangledown g](https://tex.z-dn.net/?f=%5Cbigtriangledown%20%20f%3D%5Clambda%20%5Cbigtriangledown%20%20g)
for some scalar
called the Lagrange multiplier.
For more than one restriction, say g(x,y,z)=0 and h(x,y,z)=0, the Lagrange condition is
![\bigtriangledown f=\lambda \bigtriangledown g+\mu \bigtriangledown h](https://tex.z-dn.net/?f=%5Cbigtriangledown%20%20f%3D%5Clambda%20%5Cbigtriangledown%20%20g%2B%5Cmu%20%5Cbigtriangledown%20%20h)
The gradient of f is
![\bigtriangledown f=](https://tex.z-dn.net/?f=%5Cbigtriangledown%20%20f%3D%3Cf_z%2Cf_y%2Cf_z%3E)
Considering each variable as independent we have three equations right from the Lagrange condition, plus one for each restriction, to form a 5x5 system of equations in
.
We have
![f(x, y, z) = x + 2y + 11z\\g(x, y, z) = x - y + z -1=0\\h(x, y, z) = x^2 + y^2 -1= 0](https://tex.z-dn.net/?f=f%28x%2C%20y%2C%20z%29%20%3D%20x%20%2B%202y%20%2B%2011z%5C%5Cg%28x%2C%20y%2C%20z%29%20%3D%20x%20-%20y%20%2B%20z%20-1%3D0%5C%5Ch%28x%2C%20y%2C%20z%29%20%3D%20x%5E2%20%2B%20y%5E2%20-1%3D%200)
Let's compute the partial derivatives
![f_x=1\ ,f_y=2\ ,f_z=11\ \\g_x=1\ ,g_y=-1\ ,g_z=1\\h_x=2x\ ,h_y=2y\ ,h_z=0](https://tex.z-dn.net/?f=f_x%3D1%5C%20%2Cf_y%3D2%5C%20%2Cf_z%3D11%5C%20%5C%5Cg_x%3D1%5C%20%2Cg_y%3D-1%5C%20%2Cg_z%3D1%5C%5Ch_x%3D2x%5C%20%2Ch_y%3D2y%5C%20%2Ch_z%3D0)
The Lagrange condition leads to
![1=\lambda (1)+\mu (2x)\\2=\lambda (-1)+\mu (2y)\\11=\lambda (1)+\mu (0)](https://tex.z-dn.net/?f=1%3D%5Clambda%20%281%29%2B%5Cmu%20%282x%29%5C%5C2%3D%5Clambda%20%28-1%29%2B%5Cmu%20%282y%29%5C%5C11%3D%5Clambda%20%281%29%2B%5Cmu%20%280%29)
Operating and simplifying
![1=\lambda+2x\mu\\2=-\lambda +2y\mu \\\lambda=11](https://tex.z-dn.net/?f=1%3D%5Clambda%2B2x%5Cmu%5C%5C2%3D-%5Clambda%20%2B2y%5Cmu%20%5C%5C%5Clambda%3D11)
Replacing the value of
in the two first equations, we get
![1=11+2x\mu\\2=-11 +2y\mu](https://tex.z-dn.net/?f=1%3D11%2B2x%5Cmu%5C%5C2%3D-11%20%2B2y%5Cmu)
From the first equation
![\displaystyle 2\mu=\frac{-10}{x}](https://tex.z-dn.net/?f=%5Cdisplaystyle%202%5Cmu%3D%5Cfrac%7B-10%7D%7Bx%7D)
Replacing into the second
![\displaystyle 13=y\frac{-10}{x}](https://tex.z-dn.net/?f=%5Cdisplaystyle%2013%3Dy%5Cfrac%7B-10%7D%7Bx%7D)
Or, equivalently
![13x=-10y](https://tex.z-dn.net/?f=13x%3D-10y)
Squaring
![169x^2=100y^2](https://tex.z-dn.net/?f=169x%5E2%3D100y%5E2)
To solve, we use the restriction h
![x^2 + y^2 = 1](https://tex.z-dn.net/?f=x%5E2%20%2B%20y%5E2%20%3D%201)
Multiplying by 100
![100x^2 + 100y^2 = 100](https://tex.z-dn.net/?f=100x%5E2%20%2B%20100y%5E2%20%3D%20100)
Replacing the above condition
![100x^2 + 169x^2 = 100](https://tex.z-dn.net/?f=100x%5E2%20%2B%20169x%5E2%20%3D%20100)
Solving for x
![\displaystyle x=\pm \frac{10}{\sqrt{269}}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20x%3D%5Cpm%20%5Cfrac%7B10%7D%7B%5Csqrt%7B269%7D%7D)
We compute the values of y by solving
![13x=-10y](https://tex.z-dn.net/?f=13x%3D-10y)
![\displaystyle y=-\frac{13x}{10}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%3D-%5Cfrac%7B13x%7D%7B10%7D)
For
![\displaystyle x= \frac{10}{\sqrt{269}}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20x%3D%20%5Cfrac%7B10%7D%7B%5Csqrt%7B269%7D%7D)
![\displaystyle y= -\frac{13}{\sqrt{269}}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%3D%20-%5Cfrac%7B13%7D%7B%5Csqrt%7B269%7D%7D)
And for
![\displaystyle x= -\frac{10}{\sqrt{269}}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20x%3D%20-%5Cfrac%7B10%7D%7B%5Csqrt%7B269%7D%7D)
![\displaystyle y= \frac{13}{\sqrt{269}}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20y%3D%20%5Cfrac%7B13%7D%7B%5Csqrt%7B269%7D%7D)
Finally, we get z using the other restriction
![x - y + z = 1](https://tex.z-dn.net/?f=x%20-%20y%20%2B%20z%20%3D%201)
Or:
![z = 1-x+y](https://tex.z-dn.net/?f=z%20%3D%201-x%2By)
The first solution yields to
![\displaystyle z = 1-\frac{10}{\sqrt{269}}-\frac{13}{\sqrt{269}}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20z%20%3D%201-%5Cfrac%7B10%7D%7B%5Csqrt%7B269%7D%7D-%5Cfrac%7B13%7D%7B%5Csqrt%7B269%7D%7D)
![\displaystyle z = \frac{-23\sqrt{269}+269}{269}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20z%20%3D%20%5Cfrac%7B-23%5Csqrt%7B269%7D%2B269%7D%7B269%7D)
And the second solution gives us
![\displaystyle z = 1+\frac{10}{\sqrt{269}}+\frac{13}{\sqrt{269}}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20z%20%3D%201%2B%5Cfrac%7B10%7D%7B%5Csqrt%7B269%7D%7D%2B%5Cfrac%7B13%7D%7B%5Csqrt%7B269%7D%7D)
![\displaystyle z = \frac{23\sqrt{269}+269}{269}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20z%20%3D%20%5Cfrac%7B23%5Csqrt%7B269%7D%2B269%7D%7B269%7D)
Complete first solution:
![\displaystyle x= \frac{10}{\sqrt{269}}\\\\\displaystyle y= -\frac{13}{\sqrt{269}}\\\\\displaystyle z = \frac{-23\sqrt{269}+269}{269}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20x%3D%20%5Cfrac%7B10%7D%7B%5Csqrt%7B269%7D%7D%5C%5C%5C%5C%5Cdisplaystyle%20y%3D%20-%5Cfrac%7B13%7D%7B%5Csqrt%7B269%7D%7D%5C%5C%5C%5C%5Cdisplaystyle%20z%20%3D%20%5Cfrac%7B-23%5Csqrt%7B269%7D%2B269%7D%7B269%7D)
Replacing into f, we get
f(x,y,z)=-0.4
Complete second solution:
![\displaystyle x= -\frac{10}{\sqrt{269}}\\\\\displaystyle y= \frac{13}{\sqrt{269}}\\\\\displaystyle z = \frac{23\sqrt{269}+269}{269}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20x%3D%20-%5Cfrac%7B10%7D%7B%5Csqrt%7B269%7D%7D%5C%5C%5C%5C%5Cdisplaystyle%20y%3D%20%5Cfrac%7B13%7D%7B%5Csqrt%7B269%7D%7D%5C%5C%5C%5C%5Cdisplaystyle%20z%20%3D%20%5Cfrac%7B23%5Csqrt%7B269%7D%2B269%7D%7B269%7D)
Replacing into f, we get
f(x,y,z)=2.4
The second solution maximizes f to 2.4